How many jobs? A leading indicator model of New Zealand employment - Edda Claus; Iris Claus (New Zealand Government, The Treasury, 2002)
This paper constructs a composite index of leading indicators of New Zealand employment. The choice of variables and their weights in the composite index are determined by their concordance with employment. The composite index is included in an indicator model to forecast quarterly employment growth. The indicator model explains about 67 percent of the quarterly variation in employment, in sample, and correctly predicted the direction of next period employment almost 80 percent of the time, out of sample.
Keywords: C53; E37; 330; Composite index of leading indicators; forecasting; employment